Sensitivity, specificity, inclusivity and exclusivity of the updated Aptima Combo 2 assay, which provides detection coverage of the new diagnostic-escapeChlamydia trachomatisvariants - Magnus Unemo; Marit Hansen; Ronza Hadad; Mirja Puolakkainen; Henrik Westh; Kaisu Rantakokko-Jalava; Carina Thilesen; Michelle J. Cole; Iryna Boiko; Pham T. Lan; Daniel Golparian; Shin Ito; et al. (BMC, 2022)
Background Four new variants ofChlamydia trachomatis(nvCTs), detected in several countries, cause false-negative or equivocal results using the Aptima Combo 2 assay (AC2; Hologic). We evaluated the clinical sensitivity and specificity, as well as the analytical inclusivity and exclusivity of the updated AC2 for the detection of CT andNeisseria gonorrhoeae(NG) on the automated Panther system (Hologic).
Methods We examined 1004 clinical AC2 samples and 225 analytical samples spiked with phenotypically and/or genetically diverse NG and CT strains, and other potentially cross-reacting microbial species. The clinical AC2 samples included CT wild type (WT)-positive (n = 488), all four described AC2 diagnostic-escape nvCTs (n = 170), NG-positive (n = 214), and CT/NG-negative (n = 202) specimens.
Results All nvCT-positive samples (100%) and 486 (99.6%) of the CT WT-positive samples were positive in the updated AC2. All NG-positive, CT/NG-negative,Trichomonas vaginalis(TV)-positive, bacterial vaginosis-positive, andCandida-positive AC2 specimens gave correct results. The clinical sensitivity and specificity of the updated AC2 for CT detection was 99.7 and 100%, respectively, and for NG detection was 100% for both. Examining spiked samples, the analytical inclusivity and exclusivity were 100%, i.e., in clinically relevant concentrations of spiked microbe.
Conclusions The updated AC2, including two CT targets and one NG target, showed a high sensitivity, specificity, inclusivity and exclusivity for the detection of CT WT, nvCTs, and NG. The updated AC2 on the fully automated Panther system offers a simple, rapid, high-throughput, sensitive, and specific diagnosis of CT and NG, which can easily be combined with detection ofMycoplasma genitaliumand TV.